1988
DOI: 10.1161/01.hyp.12.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Cellular hypertrophy in mesenteric resistance vessels from renal hypertensive rats.

Abstract: SUMMARY To determine whether the increased thickness seen in media of mesenteric resistance vessels of Wistar-Kyoto rats made hypertensive by a Goldblatt procedure (one-kidney, one clip model) was due to hypertrophy or hyperplasia of smooth musde cells, the cellular dimensions of these vessels were estimated using a new, unbiased stereoJogkal method (the disector). Furthermore, to investigate whether the changes seen could be secondary to the increased blood pressure, morphometric measurements were also made i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1
1

Year Published

1991
1991
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 37 publications
(33 reference statements)
5
45
1
1
Order By: Relevance
“…Since BP and R are themselves strongly correlated in this (correlation coefficient = 0.98 for 4 week group) and many other studies [21,23] their relationship to the observed spectral features is the most important result of this present study. Since these spectral features relate to the logistic function (equation (2)) which models the average spectral shape in the 350-550nm range, a connection is established between the presence of hypertension and the existence of differential absorption in the blue-green r e o n of the spectrum.…”
Section: Comparing Spectral and Morphological Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Since BP and R are themselves strongly correlated in this (correlation coefficient = 0.98 for 4 week group) and many other studies [21,23] their relationship to the observed spectral features is the most important result of this present study. Since these spectral features relate to the logistic function (equation (2)) which models the average spectral shape in the 350-550nm range, a connection is established between the presence of hypertension and the existence of differential absorption in the blue-green r e o n of the spectrum.…”
Section: Comparing Spectral and Morphological Resultssupporting
confidence: 78%
“…These effects are indeed implied by the significant correlation between R and the scaling factors for the 4-week group. In the less hypertropic 8-week group the number of correlation is reduced however significant correlations occur between b,, Al and BP, R. Since BP and R are themselves strongly correlated in this (correlation coefficient = 0.98 for 4 week group) and many other studies [21,23] their relationship to the observed spectral features is the most important result of this present study. Since these spectral features relate to the logistic function (equation (2)) which models the average spectral shape in the 350-550nm range, a connection is established between the presence of hypertension and the existence of differential absorption in the blue-green rgion of the spectrum.…”
Section: Vol 13 No 4 August 2001supporting
confidence: 66%
See 1 more Smart Citation
“…Interestingly, in this context, in essential hypertension the arterioles respond, at least initially, with hypertrophy of the myomedial cells [5,23]. In this diabetic series, we rather saw degenerative changes and the disappearance of these cells.…”
Section: Discussionmentioning
confidence: 85%
“…In PHE-and vehicle-treated mice, a further evaluation of vascular smooth muscle cell morphology was performed through the dissector technique, as described previously. 8 …”
Section: Cardiac and Vascular Remodelingmentioning
confidence: 99%